2020
DOI: 10.21924/cst.5.1.2020.182
|View full text |Cite
|
Sign up to set email alerts
|

Silylated-montmorillonite as co-adsorbent of chitosan composites for methylene blue dye removal in aqueous solution

Abstract: Industrialization plays important role in the economy of developing countries, including increasing community welfare. However, the presence of poorly industries waste disposal system has negative impact to the environment. Therefore, it is necessary to overcome this problem with low-cost technology, called adsorption. In this research, silylated-montmorillonite (sMMt) has been successfully prepared as supporting material for adsorption of methylene blue by chitosan. The sMMt was characterized by FTIR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The development of OH was found at 3402-3445 cm -1 which is the interlayer and intralayer of the H bond [30]. Saputra et al [31] also found a montmorillonite hydroxyl (OH) peak at 3434 cm -1 . Ravindra-Reddy et al [32] reported that this peak indicated the presence of water on the mineral surface.…”
Section: Effect Of Swamp Acidic Water On Sample Characterizationmentioning
confidence: 97%
“…The development of OH was found at 3402-3445 cm -1 which is the interlayer and intralayer of the H bond [30]. Saputra et al [31] also found a montmorillonite hydroxyl (OH) peak at 3434 cm -1 . Ravindra-Reddy et al [32] reported that this peak indicated the presence of water on the mineral surface.…”
Section: Effect Of Swamp Acidic Water On Sample Characterizationmentioning
confidence: 97%
“…The energy of the band gap (Eg) is required by an electron to experience an excitation from the valence band to the conduction band [27]. The energy of the band gap can be calculated with the Tauc Plot method by extrapolating the correlation graph between hv as the abscissa of axis x and (αhv) 2 as the ordinate of axis y. Tauc Plot graph for TiO2 and TiO2-M (M= Cd, Co, Mn) at the calcination temperature of 300; 400; and 500 °C is shown in Figure 4. Metal ion doping results in the decreased energy of the band gap.…”
Section: Energy Of Band Gapmentioning
confidence: 99%
“…The textile industry is one of the biggest sources of water pollution, with a large amount of dye waste [1]. The negative impacts of textile production are primarily derived from the dyeing process resulting in dye wastewater, which has a chromophore groups [2]. Dye waste disposed by waste has to be managed to prevent environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The MFA-NIC powder preparation was done by grinding what was previously reported by Fabian et al [23]. The cocrystal characterization was assessed by PXRD -a powerful tool in crystal structure alteration detection of solid material [26][27][28]. The PXRD profiles of MFA, NIC, physical mixture of MFA-NIC and its cocrystal were different from those of MFA and NIC.…”
Section: Mfa-nic Cocrystal Preparationmentioning
confidence: 99%